EP942 Incorporating tumour biology into follow-up strategies in ovarian cancer: can tumour CA125 status dictate utility of serum CA125 in the detection of recurrence?. (1st November 2019) - Nevins, E; Rundle, S; Adishesh, M; Korompelis, P; O'Donnell, RL
Abstract : Introduction/Background: Historically, patients treated for epithelial ovarian cancer (EOC) undergo long-term hospital-based follow-up with serial serum CA125 (sCA125) measurement. It is however unclear whether earlier detection of recurrence through sCA125 monitoring alters survival. This uncertainty is reflected in the variances in follow-up practices. The aim of this study was to investigate the predictive value of sCA125 at recurrence stratified by tumour CA125 (tCA125) status at diagnosis, determined by immunohistochemistry. Methodology: All patients diagnosed with EOC at the NGOC 2012– 2013 were identified from prospectively maintained data. Demographic and clinico-pathological details, including 5-year survival were collated. Correlation and survival analysis were undertaken stratified by tCA125 status. Results: 207 patients with available tCA125 underwent treatment for EOC. 176 were FIGO stage IIIC or IV and 184 were high grade serous cancers. Median sCA125 in the tCA125 positive group was 761 iu/L and in the tCA125 negative group was 151 iu/L (p=0.01). The median follow-up period was 32 months in which time 181 (87%) developed recurrent disease. sCA125 was elevated (≥ twice normal value) at relapse in 131/160 (82%) tCA125-positive group and in 4/21 (19%) tCA125-negative group. Median sCA125 at recurrence was 436 iu/L in the tCA125-positive subgroup in comparison to only 23 iu/L in the tCA125-negative group (p=0.28). Conclusion: The movement towards precision medicine with treatment pathways dictated by tumour biology is upon us and the utility of tumour biology in the diagnosis of recurrence should not be overlooked. A prospective study powered to include proportional representation of tCA125-negative patients may be justified given the substantial differences in the values demonstrated in this study. Disclosure: Nothing to disclose.